Answer:
see explanation
Step-by-step explanation:
(a)
(f + g)(x) = f(x) + g(x)
f(x) + g(x) = 6x - 2 + 2x + 4 = 8x + 2
(b)
(f - g)(x) = f(x) - g(x)
f(x) - g(x) = 6x - 2 - (2x + 4) = 6x - 2 - 2x - 4 = 4x - 6
The answer to this is: Draw a chain of bounces to the left, 12 units wide, starting at 0 and ending at -24.
This is because when you want to represent division in a number line you must always start from the zero count divisor until you reach the dividend.
The answer is: "
40 cm " .
_________________________________________________________<u>Note</u>:_________________________________________________________![\frac{200 ft }{ (x) cm} = \frac{5}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B200%20ft%20%7D%7B%20%28x%29%20cm%7D%20%3D%20%5Cfrac%7B5%7D%7B1%7D%20)
;
Solve for "x" (in "cm" ) ;
→ 5x = 200 * 1 ;
→ 5x = 200 ;
Divide each side of the equation by "5" ;
to isolate "x" on one side of the equation; & to solve for "x" ;
→ 5x / 5 = 200 / 5 ;
to get:
→ x = 40 .
___________________________________________________________The answer is: "
40 cm " .
___________________________________________________________